Blue Screen of Death: disrupting transparent windows, composite media, and the aesthetics of continuity. - Hristova, Stefka (Continuum: Journal of Media & Cultural Studies, 2017)
This article proposes that the Blue Screen of Death (BSoD), experienced on personal computers when Microsoft Windows crashes materializes technology as monitor, operating system and graphical user interface. The navy blue colour used to signal Windows’ initial interface as well as its most famous error screen points to the affinity between computers and classical Hollywood cinema. Graphic user interface (GUI) borrowed heavily from the conventions of Classical Hollywood in order to create a seamless experience out of disparate graphic elements. The computer GUI is built upon a blue screen base, much like composite cinema in the 1930s was rooted in the use of a background blue screen. In both instances, elements are stacked onto blue background in order to create a seamless experience and obscure the underpinning blue layer following an aesthetic of continuity.